The Role of Job Satisfaction in Linking Transformational Leadership, Kaizen Culture, and Public-Sector Employee Performance - Kusumawati, Indri; Sutia, Sabar; Zuhri, Saefudin (Lembaga Penelitian Universitas YARSI, 2026)
This study shows a strong correlation between transformational leadership and employee performance, both directly and through increased job satisfaction, although job satisfaction was not proven to mediate the relationship with performance. This finding implies that transformational leadership style has a strategic role in driving the performance of Public Infrastructure and Facilities Management Officers through direct influences in the form of motivation, role models, and employee empowerment, not solely through affective aspects such as job satisfaction. In contrast, Kaizen culture did not show a significant correlation with job satisfaction or performance, indicating that the implementation of continuous improvement has not been effectively internalized or has not been perceived as relevant by employees in the context of their work. The practical implication of this study is the need for organizations to prioritize strengthening transformational leadership through training and leadership development, and to re-evaluate the implementation of Kaizen culture to make it more contextual, participatory, and have a real impact on employee work activities.